Strategi-Strategi untuk Menganalisis dan Memasuki Pasar Asing Secara Sehat - Wahyuni, Sri; Ibrahim, Hendra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to find out economic strategies in facing global challenges and to find out strategies for analyzing and entering foreign markets in a healthy manner. This research uses a type of qualitative research with a library research approach. The research results show that there are 8 strategies in facing global challenges including Downstreaming and Industrialization, broad global competition, global focus, national focus, protected niche, external and internal environmental analysis, business level and company level strategies, acquisition and restructuring strategies, international strategy and strategic leadership. In an effort to enter international markets in a healthy manner, companies need to design careful and measurable strategies. This approach involves a series of in-depth economic analysis and management steps to understand the unique characteristics of foreign markets, from consumer dynamics to macroeconomic factors that may impact business operations. Competitor identification, financial risk management and collaboration with local partners are key elements in building a solid foundation for success in the global market.